A Conceptual Paper: Corporate Value Strategic Performance Implications Banking and Bank Sustainability - Aldila Dwi Septa Nawancatur; Muhammad Ja’far Shodiq (Universitas Darussalam Gontor, 2024)
Indonesia is a country with very rapid economic development, this can be seen from the increasing number of companies from year to year. In the current era of globalization, many financial institutions are growing and developing rapidly in the Indonesian economy. A high company value is the desire of company owners, because a high value shows that shareholder prosperity is also high. In the banking business, covering financial aspects alone cannot represent bank performance without evaluating the value of the impact of business activities on the environment and social as well as positive and negative performance. Apart from that, banking business units are also required to meet targets sustainability development goals(SDGs) which is the key to the sustainability of all sectors and fields in the world, so this indicates that the implementation of SDGs is very important in the eyes of the public. This research wants to test howsustainablebanks influence banking performance and company value. This research develops a causality model of the relationship between banking performance and sustainability as an independent variable, with company value as the dependent variable. In order to make the visibility of the impact of the two independent variables on company value more general and measurable, the model construction was developed by presenting company size and culture variables as control variables. The data analysis techniques used in this research are descriptive analysis and multiple linear regression analysis. Multiple linear regression analysis is an analysis to determine the effect of more than one independent variable on more than one dependent variable on the dependent variable